2015
DOI: 10.1021/acs.biochem.5b00564
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Access of Lesions to the Nucleotide Excision Repair Machinery in Nucleosomes

Abstract: In nucleosomes, the access of DNA lesions to nucleotide excision repair is hindered by histone proteins. However, evidence that the nature of the DNA lesions may play a role in facilitating access is emerging, but these phenomena are not well-understood. We have used molecular dynamics simulations to elucidate the structural, dynamic, and energetic properties of the R and S 5′-8-cyclo-2′-dG and the (+)-cis-anti-B[a]P-dG lesions in a nucleosome. Our results show that the (+)-cis-anti-B[a]P-dG adduct is more dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Within the three tertiary forms, the very low levels recorded for purine 5 0 ,8-cyclo-2 0 -deoxynucleoside lesions are in agreement with the low efficiency of such radiation-induced lesions in cellular DNA [11]. On the contrary, these lesions are harmful since they accumulate with aging in a tissue-specific manner (liver > kidney > brain) [33,41] suggesting that DNA repair mechanisms are inadequate to effectively deal with these lesions [16].…”
Section: Quantification Of Purine Lesions In Dsdna Conformersmentioning
confidence: 57%
See 1 more Smart Citation
“…Within the three tertiary forms, the very low levels recorded for purine 5 0 ,8-cyclo-2 0 -deoxynucleoside lesions are in agreement with the low efficiency of such radiation-induced lesions in cellular DNA [11]. On the contrary, these lesions are harmful since they accumulate with aging in a tissue-specific manner (liver > kidney > brain) [33,41] suggesting that DNA repair mechanisms are inadequate to effectively deal with these lesions [16].…”
Section: Quantification Of Purine Lesions In Dsdna Conformersmentioning
confidence: 57%
“…In particular, under physiological levels of oxygen (e.g. recently been studied in nucleosomes along with DNA-histone interactions and local electrostatic potentials, with emphasis on the hydrogen bond between Lys115 of histone H3 and the DNA backbone which has been observed in the case of cdG lesions [16]. Second, given the importance of non-coding repeat guanine-rich Scheme 2.…”
Section: Introductionmentioning
confidence: 99%
“…the 5′R isomer being two times more efficiently repaired by NER than the 5′S isomer [15]. Molecular modeling and dynamics simulation elucidated that the different efficiency of NER is associated with the greater DNA backbone distortion caused by the 5′R isomer compared to the 5′S diastereomer [15,16] of the lesion. It has been found that these lesions are removed with a low efficiency by NER compared to other bulky DNA adducts [14], thereby leading to the accumulation of these oxidative lesions in the genome [1,14].…”
Section: Preprintsmentioning
confidence: 97%
“…Both cdG and cdA lesions, in their 5 0 S and 5 0 R diastereomeric forms, are repaired at low efficiency by the human nucleotide excision repair (NER) pathway, there being ca. 2 times greater efficacy for 5 0 R over 5 0 S diastereomer repair, owing to greater DNA backbone distortions encountered in 5 0 R diastereomeric lesion-containing sequences [47,48]. Given the known correlation among oxidative DNA damage and its repair in trinucleotide repeats (TNR), it was investigated whether TNR instability can be induced by the cdA lesions during replication and repeat [49].…”
Section: Working Group 2: Models Of Dna Damage and Consequencesmentioning
confidence: 99%